THE IMPACT OF LAND USE CHANGE TO THE HIDROLOGICAL CONDITION OF BALANGTIENG WATERSHED - Edy Junaedi; M. Siarudin; Yongky Indrajaya; Ary Widiyanto (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Changes in land use may affect the hydrology of a watershed. This study aims to assess the hydrological conditions due to land use changes. The hydrological condition was predicted under four scenarios: (1) scenario 1, land use condition as in map 2009; (2) Scenario 2 is a change of 50% cocoa-coffee agroforestry to clove system in upstream area, and to monoculture rubber system in the middle and downstream area; (3) Scenario 3 is a change of 25% cocoa-coffee agroforestry to clove system in upstream area, and to monoculture rubber system in the middle and downstream area; (4) Scenario 4 is a change of 50% cocoa-coffee agroforestry to clove system in upstream area, and to monoculture rubber system in the middle and downstream area with a reduction of deforestation rate by 50%); and (5), Scenario 5 is a change of 25% cocoa-coffee agroforestry to clove system in upstream area, and to monoculture rubber system in the middle and downstream area with a reduction of deforestation rate by 50%. The prediction of water balance was measuredusing GenRiver model. Result shows that land use changes under scenario 1 and 2 do not affect the hydrological conditions, but need to watch out for the occurrence of flash floods. Reduction of deforestation rate in scenarios 3 and 4 can further improve the watershed hydrological conditions and maintain peak discharge during the rainy season